Safety and efficacy of Manganese chelates of lysine and glutamic acid as feed additive for all animal species. (6th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of manganese chelates of lysine and glutamic acid (Manganese‐LG) as nutritional feed additive for all animal species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) Panel was assigned to this mandate. The Panel concluded that, owing to safety considerations, the simultaneous use of both feed and water supplemented with Manganese‐LG should be avoided. Manganese‐LG showed to be safe for chickens for fattening up to the maximum authorised levels in the EU for manganese in feed (150 mg/kg); however, since a margin of safety could not be derived, the conclusions could not be extrapolated/extended to other categories/species. The data showed that Manganese‐LG does not increase nor change the patterns of manganese tissue deposition when administered up to the maximum level allowed in the EU; therefore, the Panel concluded that the additive is safe for consumers of tissues and products from animals fed the additive up to the total manganese content in feed authorised in the EU. Owing to the manganese and nickel content of Manganese‐LG, the Panel concluded that the handling of the additive poses a risk to users by inhalation and shall be considered as a skin and respiratory sensitiser; the data showed that the additive is irritant to eye and non‐irritant to skin. Manganese‐LG, intended to substitute other authorised manganese additives, will not further increase the environmental burden of manganese; the Panel considered that the use of the additive in animal nutrition would not pose an additional risk for the environment. The Panel concluded that the additive is efficacious in chickens for fattening; this conclusion can be extrapolated/extended to other categories/species. The FEEDAP Panel posed a recommendation concerning the description of the additive.